Respon Tanaman Jagung Manis (Zea Mays Saccharata Sturt) Terhadap Jumlah Benih Per Lubang dan Pemberian Pupuk Kandang Ayam - Junaidi (Jurnal Multidisiplin Madani, 2022)
The aim of the study was to determine the response of sweet corn (Zea mays saccharata sturt) to the number of seeds per hole and the application of chicken manure and their interactions. This study used a factorial design with the basic design of a Randomized Block Design (RAK). The results showed that the single factor treatment of the number of seeds per hole had a significant effect on the parameters of cob length, cob weight and the single factor of giving chicken manure with different doses had a significant effect on plant height at 30 DAP. The best treatment was given chicken manure with a dose of 20 tons/ha. While the interaction of the number of seeds per hole treatment with chicken manure gave a significant effect on the number of leaves of sweet corn plants (Zea mays saccharata sturt) aged 20 and 30 DAP